A study of fibre glass grid reinforced hot mix asphalt concrete / Sina Mirzapour Mounes - Sina Mirzapour , Mounes (2016)
Asphalt concrete is a viscoelastic material that exhibits time and temperature dependency and, except at low temperatures, viscoplastic non-recoverable strain as well as self-recovery ability in certain conditions. During the last decades, several methods such as geogrid reinforcement of asphalt concrete have been adopted by researchers to improve its characteristics. This thesis seeks to investigate some of the properties of Hot Mix Asphalt (HMA) reinforced by four different types of fibreglass grid, and unreinforced control specimens, on the basis of grid tensile strength and mesh size. In this study, the dynamic modulus of reinforced and control specimens was measured using a flexural bending beam apparatus, and the master curves for each type of specimen were constructed. The same testing aparatus with other testing conditions were used for determining the possible effect of inlaid fibreglass grids on damage recovery ability of asphalt concrete. Finally, dynamic creep test was used to investigate the behaviour of different types of asphalt concretes utilised in this study, at two different levels of load to rest ratios. In addition, a recently developed creep curve model has been verified and used to study the creep behaviour of the specimens in the primary and secondary regions of the creep curve, as well as determining the boundary point of the regions. The results of dynamic modulus test showed that, at very high frequencies or very low temperatures, the asphalt mixture bore most of the applied load and the grids were not activated. However, at very low frequencies or very high temperatures, the grids were activated and the load was borne by the grid. Moreover, at very low frequencies or very high temperatures, not only was the tensile strength of the grids effective, but the grid opening sizes also influenced the dynamic moduli of the asphalt concrete. In addition, the smaller mesh sized grids recorded much lower asymptote values. The same behaviour of grid tensile strength and mesh size was observed for the inflection points of the master curves. In terms of damage recovery ability of grid reinforced and unreinforced specimens, the results show that small mesh sized grids have a significant positive effect on the damage recovery ability of asphalt concrete, while there was little or no difference in recovery performance between the two types of tensile strength grids with large openings or the unreinforced (control) specimens. In addition, the small mesh sized grids with high tensile strength showed a higher damage recovery than the same mesh sized grids with low tensile strength. Finally, the creep test results and analysis suggest that not only grid tensile strength, but also grid mesh size is of great importance in combatting permanent deformation of the fibreglass grid reinforced asphalt concrete within the conditions and grids used in this study. In a nutshell, higher tensile strength and/or smaller mesh size grids lead to overall better performance of grid reinforced specimens. Moreover, great care must be taken when the creep curves are not reached in the tertiary region, and the creep rate must be taken into account to avoid any misinterpretation of the results.